Early language delay phenotypes and correlation with later linguistic abilities - Petinou, Kakia; Spanoudis, George (My University, 2014)
Objectives: The present study focused on examining the continuity and directionality of language skills in late talkers (LTs) and identifying factors which might contribute to language outcomes at the age of 3 years. Methods: Subjects were 23 Cypriot-Greek-speaking toddlers classified as LTs and 24 age-matched typically developing peers (TDs). Participants were assessed at 28, 32 and 36 months, using various linguistic measures such as size of receptive and expressive vocabulary, mean length of utterance (MLU) of words and number of consonants produced. Data on otitis media familial history were also analyzed. Results: The ANOVA results indicated parallel developmental profiles between the two groups, with a language lag characterizing LTs. Concurrent correlations between measures showed that poor phonetic inventories in the LT group at 28 months predicted poor MLU at the ages of 32 and 36 months. Significant cross-lagged correlations supported the finding that poor phonetic inventories at 28 months served as a good predictor for MLU and expressive vocabulary at the age of 32 and for MLU at 36 months. Conclusions: The results highlight the negative effect of early language delay on language skills up to the age of 3 years and lend support to the current literature regarding the universal linguistic picture of early and persistent language delay. Based on the current results, poor phonetic inventories at the age of intake might serve as a predictive factor for language outcomes at the age of 36 months. Finally, the findings are discussed in view of the need for further research with a focus on more language-sensitive tools in testing later language outcomes.
Keywords: Language development disorders; Early language delay; Language outcomes; Late talkers; Child, preschool; Female; Follow-Up studies; Humans; Linguistics; Aptitude; Vocabulary; Verbal behavior; Statistics as topic